( | x | − | 9 | ) | ÷ | 10 | = | ( | 11 10 | x | − | 12 | ) | ÷ | 12 |
Left side of the equation = | x | × | 1 10 | − | 9 | × | 1 10 |
= | x | × | 1 10 | − | 9 10 |
1 10 | x | − | 9 10 | = | ( | 11 10 | x | − | 12 | ) | ÷ | 12 |
Right side of the equation = | 11 10 | x | × | 1 12 | − | 12 | × | 1 12 |
= | 11 120 | x | − | 1 |
1 10 | x | − | 9 10 | = | 11 120 | x | − | 1 |
1 10 | x | − | 11 120 | x | = | - | 1 | + | 9 10 |
1 120 | x | = | - | 1 | + | 9 10 |
1 120 | x | = | - | 1 10 |
x | = | - | 1 10 | ÷ | 1 120 |
= | - | 1 10 | × | 120 |
= | - | 1 | × | 12 |
x | = | - | 12 |